Good University Governance dan Komunikasi untuk Meningkatkan Excellent Service dan Kepercayaan Mahasiswa - Siti Masumah (Mabsya: Jurnal Manajemen Bisnis Syariah, 2024)
Since its establishment, FEBI UIN SAIZU has always tried to provide the best service. So, this research objective is to determine whether GUG and communication significantly affect excellent service. To find out whether excellent service significantly affects student trust and whether GUG and communication have a significant effect on student trust through excellent service. The respondents of this research were taken based on a purposive sampling technique, with the criteria of students who had taken an introductory auditing course. The sample size in this study was 100 students taken from the Faculty of Economics and Islamic Business UIN SAIZU Purwokerto. Hypothesis testing using linear regression test and intervening regression test, which was previously tested with validity and reliability tests as well as classical assumptions consisting of normality, multicollinearity, and heteroscedasticity tests. The results of this study conclude that GUG and communication have a significant effect on excellent service. Excellent service has a significant effect on student trust. GUG and communication have no significant effect on student trust through excellent service.